2017
DOI: 10.15406/bbij.2017.05.00137
|View full text |Cite
|
Sign up to set email alerts
|

Growth in Reading Comprehension and Mathematics Achievement in Primary School: A Bivariate Transition Multilevel Growth Curve Model Approach

Abstract: Submit Manuscript | http://medcraveonline.com Reading achievement in primary school contains two distinguishable components: word reading and reading comprehension. Reading comprehension is a complex process and requires not only the fluent decoding of words but also understanding vocabulary, making inferences and relating the ideas to prior knowledge. Reading comprehension in primary schools stretches from the understanding of the meaning of words to the meaning of a short text and this is highly dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This study further supported the connection between reading comprehension and student achievement in mathematics and suggested that beginning instructional support at an earlier age strengthens the impact (Anumendem, 2017).…”
Section: Cognitive Correlation Between Reading Comprehension and Succ...supporting
confidence: 73%
See 1 more Smart Citation
“…This study further supported the connection between reading comprehension and student achievement in mathematics and suggested that beginning instructional support at an earlier age strengthens the impact (Anumendem, 2017).…”
Section: Cognitive Correlation Between Reading Comprehension and Succ...supporting
confidence: 73%
“…Glenberg et al's (2012) study supported the importance of reading comprehension strategies and the benefits found across multiple domains. Glenberg et al (2012) Studies further suggested that better reading comprehension in early grades led to better mathematic problem-solving skills in secondary grades (Anumendem, 2017;Björn et al, 2014;Cimmiyotti, 2008;Grimm, 2008;Hecht et al, 2009). This supported the importance of an effective reading comprehension program in a district and thereby validated the need to evaluate the impact of the Read 180, IStation, and Read Naturally programs in District A and the Read 180, IStation, and Rite Flight interventions in District B of the current study.…”
Section: The Role Of Reading Comprehension In Mathematicsmentioning
confidence: 99%
“…Dumay, Coe, and Anumendem (2014) found that, on average, across cohorts 74% of the total slope variance was accounted for by the school-level slope variance, whereas residual gain scores analysis showed a proportion attributable to schools of just 16% on average, across cohorts. Anumendem, De Fraine, Onghena, and Van Damme (2017) showed considerable discrepancies between intra-class correlations expressed as adjusted performance status and growth; according to one of their models, this discrepancy is as high as 0.18 for performance versus 0.66 for the growth model. Palardy (2008) reported more modest discrepancies in the intra-class correlations for performance status and growth (.20 versus .23 in the full sample, 13 versus .25 and .07 versus .14 among low-and high-scoring schools, respectively).…”
Section: School Effects In Terms Of Student Progressmentioning
confidence: 94%
“…Moreover, the term ICC is not used as an indicator of between-school differences in achievement growth. In this paper, we follow the guidelines as presented by Dumay and colleagues (2014) by calculating and presenting "the school-level slope variance as a proportion of the total slope variance" (p. 70) 1 ; a similar approach was adopted in Rowan et al (2002) and Anumendem, De Fraine, Onghena, and Van Damme (2017). Several other studies present values for between-school differences for growth rates in multilevel growth models without presenting exact descriptions of how they were calculated or providing insufficient information to reconstruct the formulas used (see Guldemond & Bosker, 2009;Raudenbush, 1989).…”
Section: Timementioning
confidence: 99%